Quercetin improves diabetic kidney disease by inhibiting ferroptosis and regulating the Nrf2 in streptozotocin-induced diabetic rats - Lei Zhang; Xingzhi Wang; Liang Chang; Yiqun Ren; Manshu Sui; Yuting Fu; Lei Zhang; Lirong Hao (Renal Failure)
Diabetic kidney disease (DKD) is a leading factor in end-stage renal disease. The complexity of its pathogenesis, combined with the limited treatment efficacy, necessitates deeper insights into potential causes. Studies suggest that ferroptosis-driven renal tubular damage contributes to DKD's progression, making its counteraction a potential therapeutic strategy. Quercetin, a flavonoid found in numerous fruits and vegetables, has demonstrated DKD mitigation in mouse models, though its protective mechanism remains ambiguous. In this study, we delved into quercetin’s potential anti-ferroptotic properties, employing a DKD rat model and high glucose (HG)-treated renal tubular epithelial cell models. Our findings revealed that HG prompted unusual ferroptosis activation in renal tubular epithelial cells. However, quercetin counteracted this by inhibiting ferroptosis and activating NFE2-related factor 2 (Nrf2) expression in both DKD rats and HG-treated HK-2 cells, indicating its renal protective role. Further experiments, both in vivo and in vitro, validated that quercetin stimulates Nrf2. Thus, our research underscores quercetin’s potential in DKD treatment by modulating the ferroptosis process via activating Nrf2 in a distinct DKD rat model, offering a fresh perspective on quercetin’s protective mechanisms.